"One Ring to Bind Them All"—Part II: Identification of Promising G-Quadruplex Ligands by Screening of Cyclophane-Type Macrocycles. (28th March 2010) - Granzhan, Anton; Monchaud, David; Saettel, Nicolas; Guédin, Aurore; Mergny, Jean-Louis; Teulade-Fichou, Marie-Paule
Abstract : A collection of 26 polyammonium cyclophane-type macrocycles with a large structural diversity has been screened for G-quadruplex recognition. A two-step selection procedure based on the FRET-melting assay was carried out enabling identification of macrocycles of high affinity (Δ T 1 / 2 up to30 ° C ) and high selectivity for the human telomeric G-quadruplex. The four selected hits possess sophisticated architectures, more particularly the presence of a pendant side-arm as well as the existence of a particular topological arrangement appear to be strong determinants of quadruplex binding. These compounds are thus likely to create multiple contacts with the target that may be at the origin of their high selectivity, thereby suggesting that this class of macrocycles offers unique advantages for targeting G-quadruplex-DNA.